(untitled) - Rae, Heather (New York, 2002)
his book examines the victimization of minority groups through history. The author argues that genocides, expulsions and forced assimilations have been the result of the efforts of rulers' wish to assert their control and legitimacy. By bringing uniformity to the populations within their boundaries, they legitimate their hold on power. This book thus shows how nationalist ideologies have influenced the form of the international state system, drawing on the experiences of Jews and Moors in Spain, Protestants in France, Armenians in Turkey, and minorities in the former Yugoslavia.
Keywords: Di cư bắt buộc,Forced migration; Lịch sử,History